Activation of ventral tegmental area vesicular GABA transporter (Vgat) neurons alleviates social defeat stress-induced anxiety in APP/PS1 mice - Yao, Di; Li, Rong; Kora, Musa; Huang, Hongqing; Liu, Xinghua; Gong, Song (Frontiers in Aging Neuroscience, 2023)
Alzheimer's disease (AD), a progressive neurodegenerative disease that manifests as cognitive impairment, is often accompanied by anxiety. Transient stress enhances the activity of VTAVgat cells for several hours, allowing them to exert a sustained sleep effect. We hypothesized that activation of VTAVgat neurons would reduce anxiety in APP/PS1 mice. We found that acute social defeat stress (SDS) led to anxiety in APP/PS1 mice, as seen in the open field test and elevated plus-arm test. Activation of VTAVgat neurons by SDS led to an increase in sleep duration, primarily due to a decrease in sleep latency and an increase in NREMs. However, the quality of sleep was poor. Chemogenetical activation of VTAVgat neurons improved sleep quality and relieved SDS-induced anxiety. The anxiety state correlated negatively with sleep duration and NREM percentage and correlated positively with theta power density in APP/PS1 mice. In conclusion, the activation of VTAVgat neurons alleviated SDS-induced anxiety in APP/PS1 mice and may be a potential way to treat anxiety in AD.